Kesehatan untuk Kedamaian dan Perdamaian Harapan dan Tantangan bagi Profesi Kedokteran - Soeprono Soeprono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1986)
Spurred by a high sense of integrity and idealism to dedicate oneself to the cause of humanity, with a well-organized fraternity encompassing the world, the medical profession is in a strong position to foster the individual's inner peace and global peace. This can be done by well-directed efforts to strengthen health for the individual, the family and the community, through vocational training and education and limitation of population growth in balance with its productivity. Also through more concerted efforts to abolish poverty and to motivate people in pursuing a better life, materially, intellectually and spiritually. To voice moral indignation at injustice, cruelty, crime, exploitation and oppression of an individual or a nation-by another individual or nation, To stress the importance for science and technology to be dedicated to peaceful uses, and to condemn the nuclear race and the use of nuclear armament in settling international conflicts. It is a duty to preserve life's environment and to contribute in building a new and better world, socially, economically and culturally, based on equality, freedom, justice and fair distribution of material and spiritual wealth. It should be realized that the pursuit of peace in the world should start with and be based upon the attainment of the individual's inner peace. Key Words: medical profession — peace studies — environmental preservation — abolishment of nuclear war — medical ethics